Sistem Pendukung Keputusan Penentuan Biji Kopi Berkualitas Menggunakan Metode Weighted Product - Ade Syahputra; Budi Arifitama (JURNAL INTEGRASI, 2023)
Coffee beans are one of the largest commodities in Indonesia, the level of consumption of coffee is increasingly in demand as time goes by the processing of coffee products consumed by the people of Indonesia. However, in determining quality coffee beans, it must comply with predetermined criteria. The different types of coffee used in the roasting and brewing process provide a different taste for each coffee produced. The purpose of this study was to determine which types of coffee beans are of high quality by using a Decision Support System approach regarding the quality of coffee beans using the Weighted Product (WP) Method. The weighted product method is used in this study because it is suitable to be applied by comparing coffee beans with the criteria they have by multiplying them to get the ranking results. The criteria in this study consisted of 5 criteria, namely, Aroma, Taste, Price, Roasting and Body. The final result of the ranking using the Weighted Product method is Sumatra coffee (0.2089), Ubud coffee (0.2082) and Kenya coffee (0.2005).